QSAR study of the DPPH radical scavenging activity of di(hetero)arylamines derivatives of benzo[b]thiophenes, halophenols and caffeic acid analogues - Lee, Adam (2012)
We performed a predictive analysis based on Quantitative Structure?Activity Relationships (QSAR) of the radical scavenging activities of a set of compounds consisting of di(hetero)arylamine derivatives of benzo-[b]thiophenes, halophenols, and caffeic acid analogues. Given the importance of this activity in medicinal chemistry it is of interest to develop a theoretical method for its prediction. The selection of the descriptors from a pool containing more than a thousand geometrical, topological, quantum-mechanical and electronic types of descriptors was performed using a new advanced version of the Enhanced Replacement Method (ERM). The best QSAR linear model was constructed using 52 molecular structures not previously used in this type of quantitative structure?property study, and showed good predictive attributes. The model analysis suggested that the activity depends on the atomic van der Waals volumes and on the atomic electronegativity; and that the conformation of the molecule does not present a relevant role in the activity.